The how of happiness : a scientific approach to getting the life you want - Lyubomirsky, Sonja (New York : Penguin Press, 2008)
Drawing on her own research with thousands of people, psychologist Lyubomirsky has pioneered a detailed yet easy-to-follow plan to increase happiness in our day-to-day lives--in the short and long term. This book that offers a guide to understanding what happiness is, and isn't, and what can be done to bring us all closer to the happy life we envision. Using more than a dozen happiness-increasing strategies, it offers a new way to understand our innate potential for joy and happiness as well as our ability to sustain it in our lives. Lyubomirsky's "happiness strategies" introduce readers to the concept of intentional activities that they can use to achieve a happier life, including exercises in optimism and how best to savor life's pleasures in the here and now. She also helps readers understand the obstacles to happiness as well as how to harness individual strengths to overcome them.--From publisher description.
I. How to attain real and lasting happiness. Is it possible to become happier -- How happy are you and why? -- How to find happiness activities that fit your interests, your values, and your needs -- II. Happiness activities. Practicing gratitude and positive thinking -- Investing in social connections -- Managing stress, hardship, trauma -- Living in the present -- Committing to your goals -- Taking care of your body and soul -- III. Secrets to abiding happiness. The five hows behind sustainable happiness: positive emotion, optimal thinking and variety, social support, motivation, effort, and commitment, habit -- The promise of abiding happiness -- If you are depressed: What is depression? -- The causes of depression -- The most effective treatments for depression -- The cure for unhappiness is happiness -- Surmounting setbacks.
Includes bibliographical references (p. [313]-357) and index.
Keywords: Happiness